Degradation of the mechanical properties of poly-lactide-caprolactone-collagen composite for pulmonary artery banding after implantation into a rat's peritoneum - Horný, Lukáš; Vištejnová, Lucie; Suchý, Tomáš; Kuželová Košťáková, Eva; Chlup, Hynek; Kronek, Jakub; Sobotka, Zbyněk; Petřivý, Zdeněk; Žaloudková, Margit; Havlíčková, Kristýna; Moláček, Jiří (Medical engineering & physics, 2025)
Pulmonary artery banding is a surgical procedure performed when there is a shunt between the left and right ventricle. Its aim is to constrict the lumen of the pulmonary artery by using a band to reduce blood flow to the lungs. In this study, we report the results of investigating the mechanical properties of a composite composed of poly(L-lactide-co-ε-caprolactone) layers and a collagen matrix (PLCL-COLL). PLCL layers were obtained by electrospinning, impregnated with collagen solution, and finally cross-linked to increase the stiffness of the material. Bands of PLCL-COLL were implanted into a rat peritoneum and explanted after 1, 3, and 6 months in vivo. The mechanical properties of the material before and after implantation were determined using uniaxial tensile tests. The same was done with samples of strips prepared from GORE-TEX material. By comparing the results of tensile tests before implantation and after explantation, it was found that PLCL-COLL degrades in the rat's body and that it exhibits a mechanical response showing of elastic modulus values that correspond well to arterial biomechanics (elastic modulus measured in the initial linear region of the deformation was found to be: 4.14 MPa ± 1.11 MPa, 2.34 MPa ± 1.02 MPa, 1.11 MPa ± 0.77 MPa, and 0.88 MPa ± 0.60 MPa before implantation, and 1, 3, and 6 months after implantation respectively). Similar to the elastic modulus, the strength of the PLCL-COLL composite decreased during in vivo exposure (1.32 ± 0.32 MPa, 0.60 ± 0.26 MPa, 0.44 ± 0.11 MPa, and 0.46 ± 0.28 MPa before implantation, and 1, 3, and 6 months after implantation respectively). In our experiments, PLCL-COLL material was always more compliant than GORE-TEX (elastic modulus 34.7 MPa ± 2.06 MPa before implantation, and 9.35 MPa ± 6.80 MPa after implantation). The results suggest that PLCL-COLL could be a suitable candidate for the development of artery banding tapes, and also for further use in cardiovascular surgery.
Keywords: Polyesters; L-lactide; Bioresorbable material; testování materiálů; Degradation; vstřebatelné implantáty; Pulmonary artery banding; krysa rodu Rattus; kolagen; zvířata; Collagen; potkani Wistar; Absorbable Implants; peritoneum; polyestery; Rats, Wistar; Male; In vivo; Elasticity; Rats; Peritoneum; Animals; arteria pulmonalis; mužské pohlaví; ε-caprolactone; Pulmonary Artery; Materials Testing